Econometric Determinants of Chinese Developmental Finance in Sub-Saharan Africa; Further Evidence Using a Flow-Type Decomposed Poisson Pseudo-Maximum Likelihood Model. (Global Journal of Human-Social Science, 2024)
Chinese “aid” has long engendered criticism. Western pundits and policymakers posit it as a political tool employed by Beijing to as way foreign policy concessions and secure natural resources access for its domestic industries, often at the expense of the recipient country. However, we argue that large amounts of these claims lack empirical scrutiny or have been hindered by enduring conceptual, methodological, and data-centric constraints. This paper thus aims to refine and integrate prevailing methodological practices to produce a more nuanced understanding of Chinese motivations. Using empirical regression analysis and a newly released granular dataset spanning 48 Sub-Saharan African countries from 2000-2021, we: (1) decompose Chinese “aid” into flow types of relative concessionality; (2) utilize a Poisson pseudo-maximum likelihood (PPML) estimator to mitigate log-transformation and hetero-skedasticity concerns present within traditional modeling of zero-inflated datasets; (3) retain a subset of contemporary values to deal with issues related to simultaneity in our regressors. Our findings suggest that while developmental goals primarily drive concessional aid, commercial lending is moreso influenced by economic self-interest, which is often incorrectly conflated with “aid” in the traditional sense. Further, Chinese “aid” does not flow disproportionately to corrupt or authoritarian regimes. This challenges the dominant “rogue donor” narrative and contributes to a more comprehensive perspective on China's emerging role in global developmental finance.
Keywords: developmental finance; concessionality; econometrics; zero-inflation; poisson pseudo-maximum likelihood (PPML)